Biosorption of Lead and Nickel by Medicago sativa (alfalfa) and Datura from Contaminated Solution - MOSAVI, S.B.; KARIMI, S.; FEIZIASL, V. (Asian Journal of Chemistry, 2010)
A series of batch adsorption experiment carried out to determine alfalfa and Datura (died biomass) biosorption capability to Pb and Ni removal from contaminated solution. Data showed that these adsorbent could remove about 94-99 % Pb and 30-50 % Ni that exist in polluted solution. However, Datura has a great affinity and capacity to metal binding compared with alfalfa. For all the metal studies, binding speed to adsorbent is high and occurred within 5 min.